O turismo de base comunitária como alternativa para o desenvolvimento sustentável: o caso da Cooperativa de Turismo e Arte na Floresta – TURIARTE em Atodi e Anã, Santarém/PA. - SANTOS, Gilmara Maria Aguiar dos (Universidade Federal do Oeste do Pará, 2024)
The study has as its theme the Community Based Tourism (CBT) applied by the Cooperative of Tourism and Art in the Forest (TURIARTE) in the communities of Atodi and Anã, Santarém/Pa, where it sought to present from the proposed general objective, a description of the actions of TURIARTE in favor of sustainable development through its activities of CBT in the communities of Anã and Atodi. In order to understand this process, the focus and justification of the present work was the recognition that the Arapiuns River region has a tourist potential. To this end, we used bibliographic, documental, field, and qualitative research. As bibliographical sources we used books, articles published in periodicals, academic papers and documents about the key concepts: sustainable development, sustainable tourism, community-based tourism and cooperativism; and about the object of study. The field research involved qualitative interviews from semi-structured scripts with 06 (six) members of the cooperative and a visit, as tourist and researcher, to the communities of Atodi and Anã, which work with TBC from TURIARTE. It is worth mentioning that the field research had to be changed due to the pandemic of COVID-19 from 2020 to 2021. As a result, TURIARTE, as a Cooperative, has been trying to establish itself and, even with ups and downs, it seeks to act in favor of its members and its final activities, having a potential to expand in order to become more and more a reference in the segments in which it operates, especially in the TBC, object of this study. And, regarding the visits to the communities of Atodi and Anã, they were an immersion and living experience where perceptions about the BCT and the challenges of this segment could become clearer, contributing to the understanding of the challenges of TURIARTE as a cooperative that operates in this segment.